Unlocking Johor's bioeconomy potential : biotechnology conference & exhibition, 25-27 August 2014, Persada Johor Convention Centre, Johor Bahru, Malaysia - Biotechnology conference & exhibition (2014 : Johor Bahru, Malaysia). (Skudai, Johor : Johor Biotechnology and Biodiversity Corporation, 2014)
4 track fields: Agbiotech, Bioindustrial, Biomedical and Policy & Financial. Includes 63 abstracts and 5 fulltexts of conference papers and posters.
E-conference manual.
Disc characteristic: CD-ROM
Title from PDF title page.
Keywords: Biotechnology -- Congresses